2016
DOI: 10.1007/s11356-016-7039-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of viable helminth ova from raw wastewater, human feces, and environmental soil samples using novel PMA-qPCR methods

Abstract: In this study, we have evaluated the efficacy of propidium monoazide quantitative polymerase chain reaction (PMA-qPCR) to differentiate between viable and non-viable Ancylostoma caninum ova. The newly developed method was validated using raw wastewater seeded with known numbers of A. caninum ova. Results of this study confirmed that PMA-qPCR has resulted in average of 88 % reduction (P < 0.05) in gene copy numbers for 50 % viable +50 % non-viable when compared with 100 % viable ova. A reduction of 100 % in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…Molecular methods are under development for detection of STH in stool and biosolids [23,24]. Additionally, two recent studies used molecular methods for detection of hookworm species and Ascaris lumbricoides in soil [25,26]. Molecular methods should be also be created and tested for detection of Ascaris and Trichuris in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular methods are under development for detection of STH in stool and biosolids [23,24]. Additionally, two recent studies used molecular methods for detection of hookworm species and Ascaris lumbricoides in soil [25,26]. Molecular methods should be also be created and tested for detection of Ascaris and Trichuris in soil.…”
Section: Introductionmentioning
confidence: 99%
“…As the PMA concentration increased from 150 to 200 lM (groups 9 and 10), the gene copy number fell by a statistically significant amount (P < 0.05), which suggested that a PMA concentration as high as 200 lM exerted toxicity towards the viable bacteria, producing a mortality rate of 63%. The toxicity could be explained by the infiltration of excessive PMA to the viable cells (Gyawali et al, 2016). Therefore, it is necessary to determine the maximum PMA concentration for specific samples, especially for manure, sludge and soil (Gyawali et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, non-human helminths parasites have been detected in fresh water [25], soil, and wastewater samples by qPCR [26]. …”
Section: Introductionmentioning
confidence: 99%